Evaluation of Pressure Pain Threshold and Active Range of Motion of TMJ and Neck in Stressed and Non Stressed Students - Gurudut, Peeyoosha; Manjula Almeida, Esha Bhadauria (International Journal of Innovative Research in Medical Science, 2016)
Objectives: - To compare the influence of naturally occurring stress in stressed and non stressed undergraduate physiotherapy students. Method: - Before the examination 222 undergraduate Physiotherapy students were screened for stress using a questionnaire, out of which 45 showed to be stressed. 37 students who were not giving the examination served as controls. These participants were assessed for PPT and AROM for Temporomandibular and cervical joints. The stressed students were assessed before examination and a week after examination. The control group was assessed only once. Results: - The values for stress were significantly high in the stressed group before exams when compared to non stressed group. The values significantly reduced in the stressed group when comparisons were made between before and after the examinations. When comparison was made after examination of the stressed group and non stressed group, the scores became insignificant. Conclusion: - The results justify direct relation between stress and muscle functions affection. Examination proved to be a natural stressor for students. However, these stress related effects are temporary and self limiting.